Senegal : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2013)
This paper on Senegal's Poverty Reduction Strategy Paper discusses the economic, social, and environmental performance of policies, the political and institutional environment, and the constraints weighing on its growth as well as the challenges to be addressed. The shortage of basic infrastructure, especially in the rural areas, is due to elevated costs and low investments. This is compounded by the high cost of individual sanitation infrastructure, the poverty of households, and the limited resources of local communities. The investment rate that sometimes reaches interesting levels remained constant at an average of around 22 percent, in real terms.